ACTIVE METHODOLOGIES IN INTERPROFESSIONAL TRAINING: EXPERIENCE REPORT OF PET-HEALTH INTERPROFESSIONALITY: Active methodologies in interprofessional training - Oliveira, Anne Araujo de Jesus; Santos, Jailton Silva dos; Duarte, Lorena dos Santos; Pinheiro, Paloma Andrade (Journal of Health Care, 2023)
Introduction: The biomedical model of health care has been replaced by the biopsychosocial model, which presents Interprofessional Education as one of its pillars, whose proposal is aimed at enhancing health actions and services, through the reorientation of the methodological conceptual bases present in the professional training process. Objective: To present active interprofessional methodologies experienced by students participating in the Education Program through Work for Health (PET-Saúde)/Interprofessionality. Methods: This is an experience report of activities developed with teaching-service-community integration actions with a workload of eight hours per week, over a period of two years, between March 2019 and March 2021. The teams were composed by tutors (teachers), preceptors (professionals in practice) and students (undergraduates in the health area. Results: Four experiences obtained through the activities developed at PET-SAÚDE/Interprofessionalidade were explained, namely: Sharing knowledge, Collective portfolio workshop, Workshop on situational diagnosis and strategic planning and role-play Conclusion: The experiences contributed to the learning of comprehensive patient care and cooperative work between different areas of knowledge, with interprofessionality, both in the academic environment and in the healthcare setting. health.
Keywords: Health education; Interprofessionality; Integrality in Health